A Sequential Study on Three Long-Period Pi2 Events Associated with Mini-Substorms - Saito, Takao; Yumoto, Kiyohumi; Aoyama, Iwao; Kamide, Yohsuke (1981)
P(論文) The smallest of the observed substorms, called mini-substorms, are found to accompany long-period (ranging from 150 to 300s) Pi2 pulsations. Worldwide and sequential features of Pi2 waves can be studied in detail by examining Pi2 events associated with mini-substorms. Three such events that occurred on December 11,1978,March 18,1974 and November 17,1971 are studied in this paper. It is found that an enhancement of Pi2 amplitude at the dayside equator takes place sequentially. World wide polarization distribution of Pi2 waves is also found to be consistent with the statistical distribution. The odd-mode model of Pi2 is substantiated. departmental bulletin paper